KHI DAN KONFIGURASI POLITIK HUKUM ORDE BARU (Vis a Vis Antara Hukum Islam dan Sistem Pemerintahan Otoriter) - Munif, Nasrulloh Ali (Ahkam: Jurnal Hukum Islam, 2015)
The discussion about the Compilation of Islamic Laws (Kompilasi Hukum Islam/KHI) never ends. There are differences among scholars in comprehending the texts because such compilation was issued in the New Order regime. In the constellation of the KHI, the product of the law appears in semi-responsive strategy. In addition, in the KHI there is a reduction of the law to a certain limit in the context of law in the country. The But political configuration Islamic law also brings impacts on the domination each other in the New Order political coniguration. Kata kunci: Kompilasi Hukum Islam, Konfigurasi Politik, Orde Baru, dan Otoriter